Evidence for a metal–bosonic insulator–superconductor transition in compressed sulfur - Kui Wang; Hongjian Zhao; Guangtao Liu; Mi Zhou; Yinqi Chen; Qiushi Li; Guangchen Ma; Hongbo Wang; Russell J. Hemley; Yanming Ma (Proceedings of the National Academy of Sciences, 2025)
The abrupt drop of resistance to zero at a critical temperature is a key signature of the current paradigm of the metal–superconductor transition. However, the emergence of an intermediate bosonic insulating state characterized by a resistance peak preceding the onset of the superconducting transition has challenged this traditional understanding. Notably, this phenomenon has been predominantly observed in disordered or chemically doped low-dimensional systems, raising intriguing questions about the generality of the effect and its underlying fundamental physics. Here, we present a systematic experimental study of compressed elemental sulfur, an undoped three-dimensional (3D) high-pressure superconductor, with detailed measurements of electrical resistance as a function of temperature, magnetic field, and current. The anomalous resistance peak observed in this 3D system is interpreted based on an empirical model of a metal–bosonic insulator–superconductor transition, potentially driven by vortex dynamics under magnetic field and energy dissipation processes. These findings offer a fresh platform for theoretical analysis of the decades-long enigmatic of the underlying mechanism of this phenomenon.